Intestinal nerve cell injury occurs prior to insulin resistance in female mice ingesting a high-fat diet - Yvonne Nyavor; Rachel Estill; Hannah Edwards; Hailey Ogden; Kaila Heideman; Kiefer Starks; Christopher Miller; George May; Lance Flesch; John McMillan; Martin Gericke; Larry Forney; et al. (Cell and Tissue Research, 2019)

Bacterial diversity in a glacier foreland of the high Arctic - URSEL M.E. SCHÜTTE; ZAID ABDO; JAMES FOSTER; JACQUES RAVEL; JOHN BUNGE; BJØRN SOLHEIM; LARRY J. FORNEY (Molecular Ecology, 2010)
Over the past 100 years, Arctic temperatures have increased at almost twice the global average rate. One consequence is the acceleration of glacier retreat, exposing new habitats that are colonized by microorganisms whose diversity and function are unknown. Here, we characterized bacterial diversity along two approximately parallel chronosequences in an Arctic glacier forefield that span six time points following glacier retreat. We assessed changes in phylotype richness, evenness and turnover rate through the analysis of 16S rRNA gene sequences recovered from 52 samples taken from surface layers along the chronosequences. An average of 4500 sequences was obtained from each sample by 454 pyrosequencing. Using parametric methods, it was estimated that bacterial phylotype richness was high, and that it increased significantly from an average of 4000 (at a threshold of 97% sequence similarity) at locations exposed for 5 years to an average of 7050 phylotypes per 0.5 g of soil at sites that had been exposed for 150 years. Phylotype evenness also increased over time, with an evenness of 0.74 for 150 years since glacier retreat reflecting large proportions of rare phylotypes. The bacterial species turnover rate was especially high between sites exposed for 5 and 19 years. The level of bacterial diversity present in this High Arctic glacier foreland was comparable with that found in temperate and tropical soils, raising the question whether global patterns of bacterial species diversity parallel that of plants and animals, which have been found to form a latitudinal gradient and be lower in polar regions compared with the tropics.

Statistical methods for characterizing diversity of microbial communities by analysis of terminal restriction fragment length polymorphisms of 16S rRNA genes - Zaid Abdo; Ursel M.E. Schüette; Stephen J. Bent; Christopher J. Williams; Larry J. Forney; Paul Joyce (Environmental Microbiology, 2006)
Summary The analysis of terminal restriction fragment length polymorphisms (T‐RFLP) of 16S rRNA genes has proven to be a facile means to compare microbial communities and presumptively identify abundant members. The method provides data that can be used to compare different communities based on similarity or distance measures. Once communities have been clustered into groups, clone libraries can be prepared from sample(s) that are representative of each group in order to determine the phylogeny of the numerically abundant populations in a community. In this paper methods are introduced for the statistical analysis of T‐RFLP data that include objective methods for (i) determining a baseline so that ‘true’ peaks in electropherograms can be identified; (ii) a means to compare electropherograms and bin fragments of similar size; (iii) clustering algorithms that can be used to identify communities that are similar to one another; and (iv) a means to select samples that are representative of a cluster that can be used to construct 16S rRNA gene clone libraries. The methods for data analysis were tested using simulated data with assumptions and parameters that corresponded to actual data. The simulation results demonstrated the usefulness of these methods in their ability to recover the true microbial community structure generated under the assumptions made. Software for implementing these methods is available at http://www.ibest.uidaho.edu/tools/trflp_stats/index.php .

Microbial macroecology: highly structured prokaryotic soil assemblages in a tropical deciduous forest - Ana M. Noguez; Héctor T. Arita; Ana E. Escalante; Larry J. Forney; Felipe García‐Oliva; Valeria Souza (Global Ecology and Biogeography, 2005)
Aim To assess the hypothesis that free‐living prokaryotes show a pattern of ‘no biogeography’ by examining the scaling of soil prokaryotic diversity and by comparing it with other groups’ biogeographical patterns. Location Two sites in the tropical deciduous forest of Chamela, Jalisco, on the western coast of Mexico. Methods We examined the diversity and distribution of soil prokaryotes in two 8 × 8 m quadrats divided in such manner that we could sample at four spatial scales. Restriction fragment length polymorphisms of 16S rRNA genes were used to define operational taxonomic units (OTUs) that we used in lieu of species to assess diversity. Results We found highly structured species assemblages that allowed us to reject multiple predictions of the hypothesis that soil bacteria show ‘no biogeography’. The frequency distribution of range size (measured as the occupancy of quadrats) of OTUs followed a hollow curve similar to that of vertebrates on continents. Assemblages showed high levels of beta diversity and a non‐random nested pattern of diversity. OTU diversity scaled with area followed a power function with slopes z = 0.42 and 0.47. Main conclusions We demonstrate a non‐ubiquitous dispersal for soil prokaryotes, which suggests a complex biogeography similar to that found for terrestrial vertebrates.

Spatial and temporal changes in microbial community structure associated with recharge‐influenced chemical gradients in a contaminated aquifer - Sheridan K. Haack; Lisa R. Fogarty; Toby G. West; Elizabeth W. Alm; Jennifer T. McGuire; David T. Long; David W. Hyndman; Larry J. Forney (Environmental Microbiology, 2004)
Summary In a contaminated water‐table aquifer, we related microbial community structure on aquifer sediments to gradients in 24 geochemical and contaminant variables at five depths, under three recharge conditions. Community amplified ribsosomal DNA restriction analysis (ARDRA) using universal 16S rDNA primers and denaturing gradient gel electrophoresis (DGGE) using bacterial 16S rDNA primers indicated: (i) communities in the anoxic, contaminated central zone were similar regardless of recharge; (ii) after recharge, communities at greatest depth were similar to those in uncontaminated zones; and (iii) after extended lack of recharge, communities at upper and lower aquifer margins differed from communities at the same depths on other dates. General aquifer geochemistry was as important as contaminant or terminal electron accepting process (TEAP) chemistry in discriminant analysis of community groups. The Shannon index of diversity ( H ) and the evenness index ( E ), based on DGGE operational taxonomic units (OTUs), were statistically different across community groups and aquifer depths. Archaea or sulphate‐reducing bacteria 16S rRNA abundance was not clearly correlated with TEAP chemistry indicative of methanogenesis or sulphate reduction. Eukarya rRNA abundance varied by depth and date from 0 to 13% of the microbial community. This contaminated aquifer is a dynamic ecosystem, with complex interactions between physical, chemical and biotic components, which should be considered in the interpretation of aquifer geochemistry and in the development of conceptual or predictive models for natural attenuation or remediation.

Enhancement of 2,4-dichlorophenoxyacetic acid (2,4-D) degradation in soil by dissemination of catabolic plasmids - Eva M. Top; Petra Van Daele; Nancy De Saeyer; Larry J. Forney (Antonie van Leeuwenhoek, 1998)